2017
DOI: 10.4293/jsls.2017.00011
|View full text |Cite
|
Sign up to set email alerts
|

Postablation Endometrial Carcinoma

Abstract: Background:Many women have undergone both resectoscopic and nonresectoscopic (or global) endometrial ablation (EA) during the past 20 years. These women are now approaching their sixth and seventh decades of life, a time frame in which endometrial carcinoma (EC) is most frequently diagnosed.Database:In several reports, surgeons have expressed concern that endometrial ablation may leave a sequestered island of EC that may escape detection, possibly delaying its diagnosis or causing it to appear at an advanced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It has been reported that EA/R could affect the clinical presentation of endometrial cancer, and that women with endometrial cancer present with pelvic pain, new‐onset vaginal bleeding, or both . However, some patients could be entirely asymptomatic .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that EA/R could affect the clinical presentation of endometrial cancer, and that women with endometrial cancer present with pelvic pain, new‐onset vaginal bleeding, or both . However, some patients could be entirely asymptomatic .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that EA/R could affect the clinical presentation of endometrial cancer, and that women with endometrial cancer present with pelvic pain, new‐onset vaginal bleeding, or both . However, some patients could be entirely asymptomatic . Regenerating endometrium persists after EA/R; therefore, it is possible that a diagnosis of endometrial cancer could be missed after EA/R because the symptoms of abnormal uterine bleeding might not manifest until the malignancy has reached its advanced stage owing to post‐EA/R scarring of the uterine cavity .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations